Estimation of body composition in competitive swimmers by means of three different techniques - Avlonitou, E.; Georgiou, E.; Douskas, G.; Louizi, A. (International Journal of Sports Medicine, 1997)
The effects of competitive swimming practice on bone mineral density (BMD), bone mineral content (BMC), and the dispersion of body fat (lean body mass and fat) were investigated. Compeitive swimmers (M = 16; F = 16) served as subjects. It was found that BMD was not affected by swimming exercise. Ss recorded lower body fat and increased lean body mass in the upper body when compared to lower extremities. Males had a more central distribution of fat than females who displayed a build-up of fat in the legs. Shoulder strength and performance were significantly related to age, BMC, and lean body mass while performance was also related to all other bone mass variables. Implication. Swimming is not a sport that will significantly reduce body fat content. Because of the excessive demands of the exercise on the upper extremities there will be an increase in lean body mass in that region. Males tend to maintain an overall distribution of body fat suggesting symmetry of development. Female swimmers increase in leg size due to fat accumulation while fat is reduced in the upper body. This is not necessarily a bad feature because the extra fat in the legs will assist the hips and legs to float higher thus facilitating streamlining.